2013
DOI: 10.2337/dc13-0468
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Circulatory Response to Hypovolemic Stress in Young Women With Type 1 Diabetes

Abstract: OBJECTIVEDiabetes is associated with hemodynamic instability during different situations involving acute circulatory stress in daily life. Young men with type 1 diabetes have been shown to have impaired circulatory response to hypovolemic stress. The effect of type 1 diabetes on cardiovascular response to hypovolemia in young women is unknown, however.RESEARCH DESIGN AND METHODSLower body negative pressure of 30 cm H2O was used to create rapid hypovolemic stress in 15 young women with type 1 diabetes (DW) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…It was also reported that cardiovascular autonomic neuropathy was involved in HI in patients with diabetes . Additionally, decreased capacitance response and decreased net fluid absorption from tissues to blood during hypovolaemic circulatory stress were associated with the pathophysiology of HI in diabetes …”
Section: Discussionmentioning
confidence: 92%
“…It was also reported that cardiovascular autonomic neuropathy was involved in HI in patients with diabetes . Additionally, decreased capacitance response and decreased net fluid absorption from tissues to blood during hypovolaemic circulatory stress were associated with the pathophysiology of HI in diabetes …”
Section: Discussionmentioning
confidence: 92%
“…Increased blood pooling in the splanchnic beds, possibly leading to increased central hypovolemia has also been detected in VVS patients (75). The central hypovolemia that occurs during orthostatic stress is compensated by mobilization of blood from peripheral capacitance vessel towards the central circulation, as well as by net capillary fluid absorption from tissue to blood in order to increase venous return to the heart and thus defend central blood volume (24,28,31,76). However, compensatory mechanisms have not been studied in VVS.…”
Section: Pathophysiology Of Vasovagal Syncopementioning
confidence: 99%
“…Reduced venous compliance at the low pressure range may also contribute to the decreased mobilization of peripheral venous blood in VVS. Compensatory redistribution of blood and fluid towards the central circulation during hypovolemic stress is a crucial defense mechanism to preserve homeostasis (24,28,30,31). Due to its large tissue mass, skeletal muscle and skin represent an important reservoir for mobilization of venous capacitance blood and net fluid absorption.…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reduced venous compliance could also be detrimental. High vessel wall compliance is mandatory for efficient mobilization of peripheral venous capacitance blood to the central circulation to uphold venous return, cardiac output, and blood pressure during an orthostatic challenge ( 12 , 13 ), We have recently presented reduced mobilization of peripheral capacitance blood in both men and women with type 1 diabetes ( 8 , 14 ), aggravated with the severity of the disease, i.e., presence of microvascular disease ( 8 ) and level of Hb A1c ( 14 ). Female gender seems especially predisposed to diabetes-associated reduction in compliance with major elastic arteries ( 15 ).…”
Section: Introductionmentioning
confidence: 99%